The Psychosocial Influences of Waiting Periods on Patients Undergoing Endoscopic Submucosal Dissection - Nagao, Noriko; Tsuchiya, Aya; Ando, Sae; Arita, Mizue; Toyonaga, Takashi; Miyawaki, Ikuko (Gastroenterology nursing, 2017)
This study aimed to clarify psychosocial influences of waiting periods on patients undergoing endoscopic submucosal dissection for cancer at an advanced medical care facility in Japan. Subjects were consenting patients hospitalized from 2009 to 2010. Qualitative and quantitative data were gathered about patients' characteristics, disease and stage, and waiting period. Qualitative content analysis was used to analyze free statements and interview data. Subjects included 154 patients with an average wait period of 46.28 days for admission. Qualitative analysis revealed the following wait period perceptions. For calmness, results indicated (1) no anxiety, (2) relief based on doctors' positive judgment, (3) whatever happens/no choice, and (4) trust in doctor. For uneasiness, perceptions included (1) the sooner, the better/eagerly waiting, (2) anxiety and concern, and (3) emotional instability. Four waiting period coping types were identified: (1) making phone inquiries, (2) busy and forgot about the medical procedure, (3) relief from anxiety, and (4) unable to function well in daily life. Patients need to be educated about cancer progression and provided an estimated wait time. They also require more information about how to manage daily life such as monitoring factors from the nursing domain including physical condition, digestive symptoms, diet, and exercise.